An assessment of landslide hazard along alternate road alignment in the Mussoorie Hills, Uttaranchal, India - Roy, Subhash Chander (Journal of Nepal Geological Society, 2003)
The Dehradun -Mussoorie area comprises a combination of the Krol-Tai formation of the doubly plunging Mussoorie Syncline. The limestone belonging to the Krol C stage of the Krol Formation is being extensively mined in the west and southwest of Mussoorie. The Main Boundary Thrust (MBT) and a large number of folds and faults affect the rocks exposed all along the Dehradun-Mussoorie Highway. There are many landslides along the highway particularly near the Kalagad Nala and Nalota Nala. These cause obstruction and problems for tourists and mine traffic along the highway. In order to ensure uninterrupted traffic and safety of tourists it became necessary to explore alternate routes for transporting the mine produce. Two of the alternate alignments identified are the Dehradun-Kiarkuli alignment and the Dehradun-Kimiari (Lambhidhar) alignment. Different levels of landsliding indices for sections of these routes were assessed and calculated on the basis of evaluation of various parameters such as lithological variation, folds and faults affecting the rock formations, hill slope angle, density of vegetation, orientation of discontinuities and extraneous activities of mining and mining traffic. The methodology adopted included assigning numerical values for various landslide hazard levels: the highest and the lowest levels being assigned 100 and zero values respectively. The Index of Landsliding for a particular section was arrived at by averaging different values assessed for these parameters. Thus, an Index of Landsliding in the range of 9l-100 represents a zone of open forests where the geological formations are thinly bedded, and/or highly jointed, dip steeply (20°-45°) and have suffered disturbance due to faulting, mining and truck traffic. A lower Index of Landsliding represents correspondingly more stable status of hill slopes. The MBT affects the rock formation along the Dehradun-Kiarkuli alignment and Dehradun-Kimiari alignment near Punkulgaon and Galjwari respectively. Phyllite, shale and quartzite exposed along parts of these alignments have suffered excessive shattering and the highest level (91-100) of landsliding. The level of Landsliding Index is also of higher order in the vicinity of the mine areas near Kiarkuli and Lambhidhar. In the context of extensive landsliding in the vicinity of the MBT and the mines, it is advisable that an equitable distribution of transport load is made over these alignments to save not only these routes but also the Dehradun-Mussoorie Highway from excessive destabilization and degradation.